1998
DOI: 10.1161/01.str.29.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Medial Smooth Muscle Cells in the Development of Saccular Cerebral Aneurysms in Rats

Abstract: The present findings indicate that there is an association between apoptosis of medial SMCs and the formation of saccular cerebral aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 30 publications
4
92
0
Order By: Relevance
“…28,30 The number of such apoptotic cells has been shown to correlate with the probability of rupture of cerebral aneurysms. 41,42 In addition to repression of SMC differentiation marker genes, KLF4 is a pluripotency factor involved in the reprogramming of somatic cells. 15 This may, in part, explain how inflammatory cells and cytokines promote vascular wall remodeling and aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…28,30 The number of such apoptotic cells has been shown to correlate with the probability of rupture of cerebral aneurysms. 41,42 In addition to repression of SMC differentiation marker genes, KLF4 is a pluripotency factor involved in the reprogramming of somatic cells. 15 This may, in part, explain how inflammatory cells and cytokines promote vascular wall remodeling and aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, collagen biosynthesis and processing was seen to be significantly inhibited in VSMC in an experimental aneurysm model (Aoki et al, 2009c). It appears that subsequent changes in the media layer include apoptosis/loss of VSMC, changes in VSMC proliferation, and thinning of the aneurysm wall (Frosen et al, 2004;Guo et al, 2007;Jayaraman et al, 2008;Kondo et al, 1998;Meng et al, 2007;Sadamasa et al, 2007;Sakaki et al, 1997;Takagi et al, 2002).…”
Section: Intracranial Aneurysms and Pathological Changes In Vascular mentioning
confidence: 99%
“…5,15,28,32,33 Hashimoto and colleagues established an experimentally induced cerebral aneurysm model in rats, and hemodynamic stress has been emphasized for aneurysmal formation. In the early stage after aneurysm induction, disruption of the elastic laminae occurs, 22,24 which is followed by infiltration of the inflammatory-related mediator to the arterial wall, and proteolytic damage to the arterial wall caused by inflammation-related mediators appears to play a crucial role. Several kinds of mediators have been reported to be decisive causes of the formation of abdominal aortic aneurysms, 13,23 and Chyatte et al demonstrated the expression of immunoglobulin, macrophages, and T-lymphocytes in humans in the walls of unruptured cerebral aneurysms.…”
Section: ©Aans 2014mentioning
confidence: 99%